Taxonomic Status of Lactic Acid Bacteria in Wine and Key Characteristics to Differentiate Species - Dicks, L.M.T.; Endo, A. (South African Journal of Enology and Viticulture, 2016)
Oenococcus oeni is the best malolactic bacterium adapted to low pH and the high SO2 and ethanol concentrations in wine. Leuconostoc mesenteroides and Leuconostoc paramesenteroides (now classified as Weissella paramesenteroides) have also been isolated from wine. Pediococcus damnosus is not often found in wine and is considered a contaminant of high pH wines. Pediococcus inopinatus, Pediococcus parvulus and Pediococcus pentosaceus have occasionally been isolated from wines. Lactobacillus brevis, Lactobacillus plantarum, Lactobacillus buchneri, Lactobacillus hilgardii (previously Lactobacillus vermiforme), Lactobacillus fructivorans (previously Lactobacillus trichoides and Lactobacillus heterohiochii) and Lactobacillus fermentum have been isolated from most wines. Lactobacillus hilgardii and L. fructivorans are resistant to high acid and alcohol and have been isolated from spoiled fortified wines. Lactobacillus vini, Lactobacillus lindneri, Lactobacillus nagelii and Lactobacillus kunkeei have been described more recently. The latter two species are known to cause sluggish or stuck alcoholic fermentations in wine. Although Lactobacillus collinoides and Lactobacillus mali (previously Lactobacillus yamanashiensis) decarboxylate L-malic acid, they are more often found in cider and fruit juices. Lactobacillus curvatus, Lactobacillus delbrueckii, Lactobacillus diolivorans, Lactobacillus jensenii and Lactobacillus paracasei are seldomly isolated from wines. Some strains of Lactobacillus casei may be closer related to Lactobacillus paracasei or a distant relative, Lactobacillus zeae. Oenococcus kitaharae, isolated from compost is genetically closely related to Oenococcus oeni, but does not decarboxylate malate, prefers higher growth pH and is phenotypically well distinguished from O. oeni. This review summarises the current taxonomic status of malolactic bacteria and lists key phenotypic characteristics that may be used to identify the species.